IDENTIFIKASI FAKTOR RISIKO GANGGUAN KESEHATAN AKIBAT KONSUMSI MI INSTAN PADA MAHASISWA UNIVERSITAS DIPONEGORO - Nurul Qodariyah; Sulistyani Sulistyani; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Instant noodles is the most consumed fast food in the worldwide. Instant noodles contain simple carbohydrates, fat and sodium. If the instant noodles is consumed continuously, it will caused obesity, increased blood sugar levels and blood pressure.The purpose of this study was to identify risk factors for health problems at the Diponegoro University students by the view of knowledge, consumption of food and instant noodles, and students characteristics. This study used observational research with cross sectional approach. The metode ofthis researchare observation, BMI (Body Mass Index) measurements, blood pressure measurements and interviews with students.The population of this studyare all students from bachelor’s degree and diploma’s degree 2015 class with total numbers of students are 8903 persons and then 105 samples are selected by proportionate random sampling technique sampling of 11 faculties. Based on this study, It showed that all students have had good knowledge about nutritious food and instant noodles, 51,4% of students consumed 2-6 packs of instant noodles in a week, 31.4% liked salty foods,14.3% are not qualified to process instant noodles, 6.7% calssified as high blood pressure, 9.5% classified as obesities, 23.8% stomachache experienced by students, 4.8% complains of nausea experienced by students,26.7% complains hard to defecate experienced by students, 8.6% of complaints of headaches experienced by students, 4.76% of complaints of diarrhea experienced by students, 1.9% of complaints students are quickly to get hungry, 3.8% of complaints bloating experienced by students, and 0,95% of complaints itchy redness experienced by students. The conclusion of this study is that all students had good knowledge, the largest instant noodle consumption is 6 packs in a week and most students complaint is hard to defecate experiencedby 26,7%  from all student complaints.